OPPORTUNITIES AND CHALLENGES OF SHARIA ACCOUNTING DEVELOPMENT - Trie Nadilla; Arifah Hidayanti (Corolla International Conference, 2022)
The universal basic principles in shariah accounting operations based al qura’an (Al Baqarah :282), namely the principle of respontibility, the principle of justice and the principle of truth. Rapid development in business activities and based financial institutions (banks, insurance, pension fund capital markets, etc.). In recent decades, financial institutions have increased the volume and value of Sharia-based transactions, which of course has increased the need for Sharia accounting. Furthermore, the development of thinking about Islamic accounting is also growing, which is marked by the increasing acceptance of the principles of Islamic transactions in the international world. This study uses descriptive analysis with the development of a conceptual model. This study analyzes various opportunities and challenges in the application of Islamic accounting. Shariah accounting there is a combination of two elements of science, namely accounting and sharia. The approaches used are the ideal approach (exploring authoritative sharia sources and then derivation) the sky approach and a pragmatic approach that uses conventional accounting to then carry out the purification process. In this approach, of course, it must be based on the maqashid sharia principle. The biggest challenge is how to break away from the conventional capitalistic financial accounting paradigm and way of thinking and then develop its own Islamic paradigm. Accountants must have expertise in technology and data analytics. Other than that, the real challenge in Islamic accounting is related to public acceptance of the concept of Islamic economics.